Hysteretic Behavior of H-Shaped Honeycombed Steel Web Composite Columns with Rectangular Concrete-Filled Steel Tube Flanges - Jing Ji; Yubo Lin; Liangqin Jiang; Wen Li; Hongguo Ren; Ruili Wang; Zihao Wang; MaoMao Yang; Chenyu Yu (Advances in Civil Engineering)
This study aims to investigate the hysteretic behavior of H-shaped honeycombed steel web composite columns with rectangular concrete-filled steel tube flanges (STHCCs). Taking the shear span ratio (λs), axial compression ratio (n), steel ratio of section (α), aspect ratio of section (D/B), yield strength of steel tube (fyfk), and compressive strength of concrete (fck) as the main parameters, we designed 22 full-scale STHCCs. By comparing the load-displacement curves between test and simulation, the rationality of finite element modeling method was verified. The quasi-static analysis of 22 specimens was carried out, and the influence regularity of different variables on the hysteretic behavior, skeleton curves, ductility, energy dissipation, resistance degradation, and stiffness degradation of STHCCs was obtained. The results show that the hysteresis curves of all the specimens show full shuttle shape and strong energy dissipation capacity. λs, α, and fyfk have great influence on the bearing capacity of skeleton curves. With the increase of α and fyfk, the initial stiffness of the specimens gradually increases. The stiffness degradation rate of the specimens gradually slows down, and the energy dissipation coefficient gradually decreases by increasing λs, α, and fyfk, but energy dissipation capacity is still at a high level. The resistance degradation of specimens increases gradually by increasing λs, α, fyfk, and D/B. The ductility of specimens gradually increases by increasing n, α, and fck. The maximum bulging deformation and maximum stress of specimens appear at the column foot. The trilinear skeleton curve model and restoring force model of STHCCs are established by statistical regression.